Development of an Intervention for Nonsuicidal Self-Injury in Young Adults: An Open Pilot Trial. Issue 4 (November 2015) - Andover, Margaret S.; Schatten, Heather T.; Morris, Blair W.; Miller, Ivan W.
Abstract: Nonsuicidal self-injury (NSSI) is a prevalent and dangerous behavior among young adults, but no treatments specific to NSSI have been developed for patients without borderline personality disorder. The purpose of this study was to develop and investigate a novel intervention for NSSI among young adults. The intervention is a 9-session behavioral treatment designed to decrease the frequency of NSSI behaviors and urges. Using an open pilot design, feasibility and acceptability were investigated in a small sample ( n = 12) over a 3-month follow-up period. A preliminary investigation of change in NSSI was also conducted. Feasibility and acceptability of the intervention were supported. Medium to large effect sizes were found for decreases in NSSI behaviors and urges over the follow up period. Results of this open pilot trial support the further evaluation of this intervention. Highlights: We developed an intervention for NSSI and investigated it in an open pilot trial. The intervention is a 9-session behavioral treatment. Feasibility and acceptability of the intervention were supported. Medium to large effect sizes were found for decreases in NSSI behaviors and urges. Results of this open pilot trial support the further evaluation of the intervention.